STRATEGI PENCAPAIAN TUJUAN-TUJUAN AFEKTIF DALAM PENDIDIKAN AGAMA ISLAM - RIDWAL TRISONI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
The teaching of Islamic education school/madrasah still faces some problems up to present. Among the problems are: Learning orientation still emphasizes cognitive aspect, cooperation between teachers of Islamic education subject and other teachers has not been well developed, methods of learning tends to be monotonous, and the like. As a result, the goals of Islamic education subject which should focus more on affective aspects seems to be ignored. Consequently, many students know much about Islamic education subject but they know very little about the implementation in real life. In order that the affective goal of Islamic education subject can be realized, various strategies are urgently reeded. Among those strategies, beside teaching the subject in isolated way, integrating to all subjects, creating religions atmosphere within the schools/madrasah, and societies are highly recomm ended onesKata kunci: strategi, afektif, nilai, ahklak